A CONCEPTUAL RESEARCH ON THE EVALUATION OF RURAL TOURISM AND ORGANIC FARM POTENTIAL IN GAZIANTEP - Abdullah AKMAZ (Fırat University, 2019)
Factors such as the intense working conditions of people, the desire to move away from the concrete city life, the desire to reduce the pressure created by external factors such as noise, and the attractiveness of the nature, lead people to the calm places in the nature where they can relax. However, organic agricultural products need to be consumed in terms of people's health. In addition, organic agriculture has many positive effects in the region. In addition to organic agriculture, there are environmental, social, economic and organizational / institutional benefits in the region. Today, tourism has gone beyond sea, sun and sand. Turkey is one of the leading sectors of the economy is unavoidable to uncover new benefits of organic farming, which combines with tourism. This study focuses on the evaluation of rural tourism and organic farming potential in Gaziantep. In addition, the idea that the local people of Gaziantep will provide more economic benefits than tourism and organic agriculture is included. At the same time, it has been concluded that Gaziantep is able to obtain more important opportunities by strengthening the places where it is weak except for the strengths in rural tourism and organic agriculture. Organic agriculture and rural tourism, the environment, the negative effects on human health can be reduced and rural tourism can be developed in Gaziantep.